On the investigations of Kiril Popoff in the field of ballistics (in Bulgarian) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2008)
A short survey on the main results of Kiril Popoff in the field of ballistics is presented. Special attention is given to the affine transformations of the gravity center trajectories and the shell rotations around its gravity center.